Предмет: Математика,
автор: oleg3207
нужно упростить
5/6(2,4x+6/35y)-1,2(2/3y-5/7y)
Ответы
Автор ответа:
0
= (2,4 * 5 : 6)х + (5/6 * 6/35)у - (1,2 * 2 : 3)х + (1,2 * 5)/7у =
= 2х + 1/7у - 0,8х + 6/7у = (2х - 0,8х) + (1/7у + 6/7у) = 1,2х + 7/7у =
= 1,2х + у
= 2х + 1/7у - 0,8х + 6/7у = (2х - 0,8х) + (1/7у + 6/7у) = 1,2х + 7/7у =
= 1,2х + у
Похожие вопросы
Предмет: Математика,
автор: valeria7539
Предмет: Геометрия,
автор: polina2116sfgx
Предмет: География,
автор: thebestbrawler07
Предмет: История,
автор: 0l3G
Предмет: Математика,
автор: shibaka